2015
DOI: 10.1177/1934578x1501000629
|View full text |Cite
|
Sign up to set email alerts
|

Normonanchocidins A, B and D, New Pentacyclic Guanidine Alkaloids from the Far-Eastern Marine Sponge Monanchora pulchra

Abstract: New pentacyclic guanidine alkaloids, normonanchocidins A, B and D (1-3) along with the earlier known monanchocidin A were isolated from the Far-Eastern marine sponge Monanchora pulchra. Structures of 1-3 were elucidated using 1D-and 2D-NMR spectroscopic and mass spectrometric data. Compound 1 and a mixture of 2 and 3 (1:1) exhibited cytotoxic activities against human leukemia THP-1 cells with IC 50 values of 2.1 µM and 3.7 µM, respectively, and against cervix epithelial carcinoma HeLa cells with IC 50 of 3.8 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Pentacyclic guanidine alkaloids (PGAs) are a class of biologically active secondary metabolites found in tropical and Far-Eastern marine sponges [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Their structures conventionally distinguish three structural blocks, such as: "vessel" part, "anchor" part and polymethylene chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pentacyclic guanidine alkaloids (PGAs) are a class of biologically active secondary metabolites found in tropical and Far-Eastern marine sponges [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Their structures conventionally distinguish three structural blocks, such as: "vessel" part, "anchor" part and polymethylene chain.…”
mentioning
confidence: 99%
“…The polycyclic part contains a new structural element, an n-propyl group attached to C-19. Most recently, the isolation was reported of three new PGAs from the sponge M. pulchra, named normonanchocidins having a new type of "anchor" part, a derivative of 1,3-diaminopropane [17].…”
mentioning
confidence: 99%
“…In the past decade, the isolation of several potent PGA families from the marine sponge Monanchora pulchra has reignited the desire to explore the treasure trove of biology surrounding these exciting natural products. 1822 In particular, cellular mechanisms regarding how PGAs affect cancer cells have been the subject of study recently due to their potential exploitation in antitumor therapy; however, the detailed function at a molecular level remains largely unknown, with several hypotheses and limited model studies. Herein, we wish to summarize the previous studies on the mechanism of action of PGAs.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…in 1989 by Kashman and co-workers. 11 In the following years, several PGA families, namely the crambescidins 12–15 , neofolitispates 16 , fromiamycalin 17 , celeromycalin 17 , monanchocidins 18,19 , monanchomycalins 20,21 and normonanchocidins 22 have been isolated, primarily from marine sponges and other aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years it has been shown that the far-eastern marine sponge Monanchora pulchra is also a rich source of novel pentacyclic [3,4,5,6,7], bicyclic [8] and acyclic guanidine alkaloids [9,10]. It is interesting that alkaloids produced in the sponges from different locations and depths had a variety of structures.…”
Section: Introductionmentioning
confidence: 99%